Causal associations of male infertility with stroke: a two-sample Mendelian randomization study - Zhu, Yutian; Xin, Xiyan; Yu, Ziyang; Guan, Siqi; Wang, Jingshang; Liu, Qiuning; Dong, Lei; Ye, Yang (Frontiers in Endocrinology, 2024)
Background: Stroke is a devastating global health issue, with high mortality and disability rates. The increasing prevalence of male infertility among reproductive-aged men has become a growing concern worldwide. However, the relationship between male infertility and stroke incidence remains uncertain. This study aimed to address this knowledge gap by employing a Mendelian randomization (MR) approach.Method: Utilizing genetic instrumental variables derived from a genome-wide association study (GWAS) on male infertility and stroke, a two-sample MR design was implemented. Five different analysis methods, with inverse-variance weighted as the primary approach, were used to examine the genetic causal associations between male infertility and various stroke subtypes.Heterogeneity analysis, pleiotropy tests, and leave-one-out validation were conducted to assess heterogeneity, evaluate pleiotropy, and ensure the robustness of the findings.The results indicate a potential lower risk of small vessel stroke associated with male infertility (odds ratio, 95% confidence interval: 0.82, 0.68 to 0.99, p=0.044), although no significant impact on other stroke subtypes was observed. The study exhibited low heterogeneity and no apparent pleiotropy; however, the stability of the results was not optimal.Male infertility might potentially confer a protective effect against small vessel stroke risk. Caution is warranted due to potential confounding factors. Additional studies are necessary to confirm these findings and provide further validation.